Anthocyanins from Lycium ruthenicum Murray Inhibit HepG2 Cells Growth, Metastasis and Promote Apoptosis and G2/M Phase Cycle Arrest by Activating the AMPK/mTOR Autophagy Pathway. (30th December 2022) - Fan, Hongli; Ji, Yonggan; Wang, Yang; Liu, Danni; Wei, Tingting; Cao, Xue; Yang, Mengmeng; Bai, Changcai; Wang, Zhisheng
Abstract : Among the most common malignancies in humans, liver cancer ranks third in terms of mortality in the world. Seeking new anticancer drugs or adjuvant chemotherapy drugs from natural products has attracted the attention of many researchers. Lycium ruthenicum Murray (LR), a health food and traditional Chinese medicine, exerts extensive pharmacological properties, of which anthocyanins are one of the key active components. In this research, we explored the antitumor activity and autophagy regulation mechanism of anthocyanins from Lycium ruthenicum Murray (ALR) in HepG2 cells. Our results found that ALR profoundly reduced the cell viability, clone formation, migration, and invasion and promoted apoptosis and G2/M phase arrest of HepG2 cells in a dose-dependent pattern. Further studies confirmed that ALR treatment significantly increased the number of autophagic vacuoles and autophagosomes, upregulated the expression of Beclin-1, p62, LC3-II/LC3-I, and p-AMPK, and concomitantly downregulated the expression of p-mTOR. When autophagy was inhibited by 3-methyladenine (3-MA), ALR-induced proliferation inhibition, invasion, and migration capabilities, as well as apoptosis rate and G2/M phase arrest, were all reversed, and the activities of key proteins in the AMPK/mTOR pathway were all constrained. In summary, the results presented here indicate that ALR may be effective as a natural antitumor agent by activating AMPK and inhibiting the mTOR autophagy pathway in HepG2 cells.